Fluorescence detection and removal of copper from water using a biobased and biodegradable 2D soft material. Issue 2 (8th December 2017) - Li, Meng; Liu, Zhijiang; Wang, Shuwen; Calatayud, David G.; Zhu, Wei-Hong; James, Tony D.; Wang, Lidong; Mao, Boyang; Xiao, Hui-Ning
Abstract : We have developed a green and robust fluorogenic ( λ ex = 410 nm, λ em = 510 nm) cellulose membrane using graphene oxide (GO) as a construct for simultaneous copper ion recognition and filtration at environmentally relevant levels. Abstract : We have developed a green and robust fluorogenic ( λ ex = 410 nm, λ em = 510 nm) cellulose membrane using graphene oxide (GO) as a construct for simultaneous copper ion recognition and filtration at environmentally relevant levels. The detection limit and removal limit of Cu 2+ are 7.3 × 10 −7 M and 1000 ppm, respectively. The simplicity and scalability achieved for the detection and removal of metal ions in waste water is particularly noteworthy given the significant problems associated with metal ion pollution of drinking water.